Designing With Clay: Architectural Evaluation of Hollow and Solid Brick for Sustainable Construction - Shrestha, Reeti; Yadav, Shreya; Adhikari, Siyusha; Baral, Sudikshya; Shrestha, Kailash (KEC Journal of Science and Engineering, 2026)
This paper evaluates the environmental, thermal, and structural performance of solid and hollow clay bricks in a building. We evaluate compressive strength, thermal insulation, and carbon footprint using material testing and case studies (such as Auroville Visitors Centre, IIT Hyderabad). According to the findings, hollow clay bricks preserve structural integrity while using 20–30% less energy than solid bricks. There are suggestions for the best brick choices based on climate zones.